Linking Competence and Work Discipline to Employee Performance Through Job Satisfaction Mediation - Anwar, Syamsul; Suripno, Suripno; Sitanggang , Rohana (Journal of Economics and Management Scienties, 2025)
This study examines the effect of competence and work discipline on employee performance with job satisfaction as an intervening variable at the Department of Transportation, Agam Regency, West Sumatra. The research employed a quantitative design with a census sampling method, involving all 70 employees as respondents. Data were collected using structured questionnaires and analyzed using SmartPLS 4.0 with the SEM–PLS approach. Results revealed that both competence and work discipline have significant positive effects on employee performance, with discipline emerging as the strongest direct predictor. Competence and discipline also positively influenced job satisfaction, which in turn significantly enhanced performance. Mediation analysis confirmed that job satisfaction partially mediated the relationship between competence and performance, as well as between discipline and performance, with stronger effects observed for discipline. These findings highlight that employee performance improvement requires not only technical competence and behavioral discipline but also psychological satisfaction at work. The study contributes theoretically by extending human resource management literature in the public sector and practically by offering actionable insights for policymakers to strengthen discipline systems, align competencies with job roles, and enhance satisfaction through recognition and career development.